If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 37 = 1 + 5x Reorder the terms: 37 + x = 1 + 5x Solving 37 + x = 1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 37 + x + -5x = 1 + 5x + -5x Combine like terms: x + -5x = -4x 37 + -4x = 1 + 5x + -5x Combine like terms: 5x + -5x = 0 37 + -4x = 1 + 0 37 + -4x = 1 Add '-37' to each side of the equation. 37 + -37 + -4x = 1 + -37 Combine like terms: 37 + -37 = 0 0 + -4x = 1 + -37 -4x = 1 + -37 Combine like terms: 1 + -37 = -36 -4x = -36 Divide each side by '-4'. x = 9 Simplifying x = 9
| 13.35=logx | | -5x+9=4(5-x) | | 6(2l+7)=54 | | 2f-1=9 | | 159.7=5(0.05m+21.8+0.3(21.8)) | | 16k^2-8k-24=0 | | a=at-0.25vt^2 | | 14-(-6)= | | 5(a-5)=45 | | 570=650-8x | | 7x-4(2x+8)+15=12+2x-8 | | Y=e^4ln(x) | | -14-(-6)= | | x^4+4x-126=0 | | 3x+y-2z=4 | | 3x=9x+4 | | -2(p-4)=2p+8 | | 20x+10=900 | | 4x+5y+6z=24 | | 203.95=5(0.7m+28.80+0.20(28.8)) | | 2y^4-2x^4y^4= | | -4(2x-3)=-12-2x | | 9z+1=4 | | 15n-62= | | 0=-4(2x-3) | | 83=4(5x-8)+3x | | -7x+12=2x-13 | | 0=x^2+26x+169 | | 2+(2-6)-2=-10 | | 5x+8*4+8*16=-20 | | -5(11)+9=4(5-11) | | 2x+3(x-1)=10 |